2013
DOI: 10.5267/j.msl.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of intellectual capital on organizational performance measurement through organizational learning capabilities

Abstract: During the past few years, there have been growing interests on intellectual capital due to industrial changes on the market. Thus, identifying different ways to create, manage, and evaluate the impact of intellectual capital has remained an open area of research. One of the most important organizational capabilities, which could help organizations create and share knowledge is to effectively use knowledge to create competitive advantage. The primary objective of this study is to investigate the effects of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…They reported that there was a significant relationship between organizational agility and two dimensions of organizational structure but they did not find any relationship between complexity and organizational agility. Darvish et al (2013) investigated the impacts of intellectual capital on other components and their impacts on organizational learning capability. Their results of this survey indicated that human capital, relational capital and learning capabilities had positive influence on organizational performance, relational capital positively impacted learning capability and human capital influenced positively on relational capital.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that there was a significant relationship between organizational agility and two dimensions of organizational structure but they did not find any relationship between complexity and organizational agility. Darvish et al (2013) investigated the impacts of intellectual capital on other components and their impacts on organizational learning capability. Their results of this survey indicated that human capital, relational capital and learning capabilities had positive influence on organizational performance, relational capital positively impacted learning capability and human capital influenced positively on relational capital.…”
Section: Introductionmentioning
confidence: 99%
“…One of essential organizational capabilities, which help organizations create and share knowledge, is to implement knowledge to create competitive advantage. Darvish et al (2013) investigated the impacts of intellectual capital on other components and their effects on organizational learning capability. They reported that human capital, relational capital and learning capabilities had positive impact on organizational performance.…”
Section: Introductionmentioning
confidence: 99%
“…Organizational learning could be gained through human capital or structural and helps people build better relationships and cooperation. Darvish et al (2013) investigated the impacts of intellectual capital on other components and their effects on organizational learning capability. They reported that human capital, relational capital and learning capabilities had positive effect on organizational performance and relational capital positively impacted learning capability and human capital influenced positively on relational capital.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present an empirical study to re-examine the previously published work by Darvish et al (2013) using structural equation modeling. The organization of this paper first presents details of the hypotheses in section 2 and section 3 presents details of our results.…”
Section: Introductionmentioning
confidence: 99%